2021
DOI: 10.3390/cryst11050505
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Astaxanthin on Chronic Diseases

Abstract: Natural astaxanthin exists widely in algae, fungi, shrimp and crab, and, as a strong antioxidant, has potential effects on cardiovascular diseases, cancer, liver diseases and other physical health diseases. The treatment of many diseases involves the body’s signal transduction to regulate the body’s antioxidant defense system and inflammation. Astaxanthin is usually used as a dietary supplement, which plays an antioxidant and anti-inflammatory role in the organism. This article reviews the structure, source of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 98 publications
1
17
0
Order By: Relevance
“…Hyperglycemia triggers various degenerative and inflammatory healthy complications. Numerous studies have demonstrated beneficial effects of ASTX on diabetes-associated chronic diseases [16]. Several studies indicate that in addition to anti-inflammatory and antioxidative effects, ASTX attenuates hyperglycemic conditions in diabetic animal models [26].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hyperglycemia triggers various degenerative and inflammatory healthy complications. Numerous studies have demonstrated beneficial effects of ASTX on diabetes-associated chronic diseases [16]. Several studies indicate that in addition to anti-inflammatory and antioxidative effects, ASTX attenuates hyperglycemic conditions in diabetic animal models [26].…”
Section: Discussionmentioning
confidence: 99%
“…While hyperglycemia causes oxidative stress and inflammatory activation, inflammatory response itself also stimulates cellular ROS generation and accumulation [2,16]. To further explore the possible mechanisms by which ASTX protects diabetes-triggered periodontal destruction, we determined the expression levels of several markers corresponding to oxidative stress, DNA damage, and inflammation in periodontal tissue samples by IHC.…”
Section: Astx Attenuates Stz-induced Oxidative Damage and Inflammatory Response In The Periodontium Of Diabetic Micementioning
confidence: 99%
See 3 more Smart Citations